USE OF POCKETBOOKS AS PARENTS' GUIDELINES IN MAINTAINING THE DENTAL AND MOUTH CLEANLINESS OF CEREBRAL PALSY CHILDREN - Endah Aryati Ekoningtyas; Nanda Bupa Pratama; Bedjo Santoso (Wealth Community Empowerment, 2025)
Dental and oral health problems are often experienced by children with special needs. Limitations in physical and mental development can affect the process of maintaining dental and oral health. Children with special needs in the disabled group have disorders where their body parts are not perfect because they experience disabilities caused by damage to the bones, muscles, and joints so that they do not function normally. The shortcomings of children with physical impairments require parental assistance in maintaining dental and oral health. Providing counseling and giving pocketbooks to parents is an alternative to strengthening the maintenance of dental and oral health for children with physical impairments. This community service activity was carried out at SLB Jepara on a sample of children with physical impairments. The method used in this activity is the Health system approach, namely: Input – Process – Output. The results of the service carried out showed a decrease in the debris index value in children. The good debris index category after implementation was obtained by all respondents. The dental and oral hygiene pocketbook for parents of physically disabled children is used as a tool to increase parents' knowledge about dental and oral health and hygiene.